Pollution abatement of heavy metals in different conditions by water kefir grains as a protective tool against toxicity - Volpi, Giorgio; Ginepro, Marco; Tafur-Marinos, Janeth; Zelano, Vincenzo; Goulas, Vlasios (My University, 2019)
This research paper addresses the hypothesis that Water Kefir grains can be used as absorbers of metal ions and reports the first application of the Water Kefir grains as a protective tool against toxicity by heavy metal ions. The aim of this study is to evaluate the concentration of heavy metal ions in several Water Kefir solutions during the fermentation process under various conditions. Two colonies of Water Kefir grain were used, and the concentrations of Cd, Co, Cr, Cu, Mn, Ni, Pb, Ba, and Ca were measured in Water Kefir grain solutions at different contact times (0, 24, 48, and 72 hours), different pH values in citric and acetic buffers, and different Water Kefir grains/metal solution ratios, with and without sucrose (5%). Optical emission spectroscopy was used to measure the concentrations of metal ions. Among the tested experimental conditions, the best combination for pollution abatement is sucrose (5%), contact time 24 hours, starting pH = 4.5, acetate buffer, and Kefir grains/metal solution ratio 1: 1. In these conditions, the heavy metal abatement by Water Kefir grains is particularly effective for Cr and Pb (70%) and good for Cu, Ni, and Mn (50%).
Keywords: Cultured Milk Products; Kefir; Kefir grain